Differential contribution of THIK-1 K+ channels and P2X7 receptors to ATP-mediated neuroinflammation by human microglia - Ali Rifat; Bernardino Ossola; Roland W. Bürli; Lee A. Dawson; Nicola L. Brice; Anna Rowland; Marina Lizio; Xiao Xu; Keith Page; Pawel Fidzinski; Julia Onken; Martin Holtkamp; et al. (Journal of Neuroinflammation, 2024)
Abstract Neuroinflammation is highly influenced by microglia, particularly through activation of the NLRP3 inflammasome and subsequent release of IL-1β. Extracellular ATP is a strong activator of NLRP3 by inducing K+ efflux as a key signaling event, suggesting that K+-permeable ion channels could have high therapeutic potential. In microglia, these include ATP-gated THIK-1 K+ channels and P2X7 receptors, but their interactions and potential therapeutic role in the human brain are unknown. Using a novel specific inhibitor of THIK-1 in combination with patch-clamp electrophysiology in slices of human neocortex, we found that THIK-1 generated the main tonic K+ conductance in microglia that sets the resting membrane potential. Extracellular ATP stimulated K+ efflux in a concentration-dependent manner only via P2X7 and metabotropic potentiation of THIK-1. We further demonstrated that activation of P2X7 was mandatory for ATP-evoked IL-1β release, which was strongly suppressed by blocking THIK-1. Surprisingly, THIK-1 contributed only marginally to the total K+ conductance in the presence of ATP, which was dominated by P2X7. This suggests a previously unknown, K+-independent mechanism of THIK-1 for NLRP3 activation. Nuclear sequencing revealed almost selective expression of THIK-1 in human brain microglia, while P2X7 had a much broader expression. Thus, inhibition of THIK-1 could be an effective and, in contrast to P2X7, microglia-specific therapeutic strategy to contain neuroinflammation. Graphical Abstract